2008
DOI: 10.1093/ndt/gfn505
|View full text |Cite
|
Sign up to set email alerts
|

Body mass does not have a clinically relevant effect on cystatin C eGFR in children

Abstract: In children, body mass exerts a minimal effect on the performance of CysC eGFR estimation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
29
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 14 publications
4
29
1
1
Order By: Relevance
“…In children, age and body mass do not significantly affect cystatin C eGFR (13). The known confounders affecting cystatin C levels such as corticosteroids and thyroid status cannot explain the variability in the performance of different cystatin C equations either (3,8,11).…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…In children, age and body mass do not significantly affect cystatin C eGFR (13). The known confounders affecting cystatin C levels such as corticosteroids and thyroid status cannot explain the variability in the performance of different cystatin C equations either (3,8,11).…”
Section: Introductionmentioning
confidence: 88%
“…The known confounders affecting cystatin C levels such as corticosteroids and thyroid status cannot explain the variability in the performance of different cystatin C equations either (3,8,11). Previous studies have demonstrated that the variance between cystatin C eGFR and measured GFR increases in the high GFR range when compared with that in the low GFR range (3,13). The cystatin C eGFR estimates by different equations also show a higher interequation variability at a higher GFR (14).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, serum creatinine is largely affected by maternal GFR as creatinine crosses the placenta [8]. Over the last decade, cystatin C, a low molecular weight cysteine protease that is constantly produced by all nucleated cells [9], has evolved as a promising alternative to serum creatinine, with a better diagnostic sensitivity [10] and independence of muscle mass [11] and body composition [12]. Currently, the best estimated (e)GFR formulae in children can be derived from cystatin C alone or in combination with creatinine and/or urea [13].…”
Section: Introductionmentioning
confidence: 99%